Chemo-immune synergetic therapy of esophageal carcinoma: trastuzumab modified, cisplatin and fluorouracil co-delivered lipid-polymer hybrid nanoparticles - Qingxia Fu; Jiancheng Wang; Hong Liu (Taylor & Francis Group, 2020)
Esophageal cancer is the sixth most common cause of cancer-related death worldwide. Peptide modified nanoparticles have been engineered as novel strategies to improve esophageal adenocarcinoma (EAC) therapy. This study aimed to develop a trastuzumab (TAB) modified system for the delivery of cisplatin (CIS) and fluoropyrimidine (5-FU). In the present study, CIS and 5-FU co-encapsulated lipid-polymer hybrid nanoparticles (CIS/5-FU LPHNs) were prepared. TAB was conjugated to the surface of CIS/5-FU LPHNs to achieve TAB decorated CIS/5-FU LPHNs (TAB-CIS/5-FU LPHNs). After the in vitro assessment, a subcutaneous model was used for the in vivo study. The mean diameter of LPNHs was around 100 nm, with higher encapsulation efficacy (EE) of about 90%. The LPNHs was stable and able to release drugs in sustained manners. 63.9% of cell uptake was achieved by TAB-CIS/5-FU LPHNs, with the best in vivo antitumor ability. The best synergistic effect with the lowest CI value (0.68) was achieved at the ratio of 1/1, which was determined for the dosage of drugs in the LPHNs preparation. TAB-CIS/5-FU LPHNs provide a new strategy for synergistic treating of EAC with higher efficacy and reduced side effects, introducing this system as a candidate for EAC therapy.